Protecting group directed ring-closing metathesis (RCM): the first total synthesis of an anti-malarial nonenolide - Mohapatra, Debendra K.; Ramesh, Dhondi K.; Giardello, Michael A.; Chorghade, Mukund S.; Gurjar, Mukund K.; Grubbs, Robert H. (Tetrahedron Letters, 2007)
The first synthesis of a newly found naturally occurring anti-malarial nonenolide is described. A pivotal step in the synthesis is the ring-closing metathesis of a dienoic ester prepared by coupling an acid and alcohol that were stereoselectively synthesized from (S)-alpha-hydroxy-gamma-butyrolactone and 1,2-O-isopropylidene D-glyceraldchyde, respectively. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: 1; 2-O-isopropylidene; anti-malarial agent; D-glyceraldehyde; Nonenolide; Ring-closing metathesis; Yamaguchi esterification

Total syntheses and absolute stereochemistry of decarestrictines C-1 and C-2 - Mohapatra, Debendra K.; Sahoo, Gokarneswar; Ramesh, Dhondi K.; Rao, J. Srinivasa; Sastry, G. Narahari (Tetrahedron Letters, 2009)
The total syntheses of decarestrictines C-1 and C-2 have been described. The synthetic strategy involves a practical and flexible approach using esterification and ring-closing metathesis to unite the acid and alcohol fragments. The acid fragments are enantiomers of each other and have been prepared from L-(-)-malic acid via similar transformations; in Sharpless asymmetric epoxidation, (+)-DET has been used for decarestrictine C-1 and (-)-DET for decarestrictine C-2. The alcohol fragment is identical for both decarestrictines C-1 and C-2 and has been accessed from D-(+)-mannitol. Comparison of the H-1 and C-13 NMR data combined with the computational studies predicts the presence of two conformations without and with hydrogen bonding (conformational isomers I and II for decarestrictine C-1), respectively. The H-1 and C-13 NMR data for decarestrictine C-2 completely agreed with the analytical data reported by Kibayashi et al. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Decarestrictines; Pinnick oxidation; Ring-closing metathesis; Sharpless asymmetric epoxidation; Yamaguchi coupling reaction